Evaluation of heart rate index equations for prediction of maximal oxygen uptake in healthy adolescent boys: Cross-validation by respiratory gas analysis method - Eelahe Shadabnik; Farzad Nazem; Majid Jalili (Shahid Beheshti University, 2023)
Background and Purpose: Accurate measurement of cardiorespiratory fitness (VO2max) is very important in sport sciences. The direct measurement of VO2max using a respiratory gas analysis device cannot be very operational and comprehensive due to the high cost, time-consuming, need for an expert, and the possibility of some cardio-respiratory risks during the performance of an increasing exercise test. Estimating VO2max using equations based on heart rate index (HRindex) is one of the most widely used methods in sports fields, which can estimate an individual's VO2max without needing breath gas analysis. However, this requires accurate measurements of resting and maximal heart rates with the least error. In the present study we aimed to evaluate the validity of VO2max equations based on heart rate index in adolescent boys. Material and Methods: One hundred and fifty-seven healthy adolescent boys (Mean±SD; age, 14.92±1.35 years; BMI, 21.39 ± 4.50 kg/m2 and VO2max: 41.80 ± 6.67 ml/kg/min) from middle and high schools in Hamadan city voluntarily participated in this cross-sectional study. Initially, the resting heart rate and body composition of the subjects were measured. The subjects' VO2max and maximal heart rate were measured by the respiratory gas analysis method by using modified Bruce incremental exercise test (criterion method). Moreover, the subjects' VO2max were estimated using HRindex-based equations. Pearson correlation, pair sample t-test, and Bland and Altman agreement were used to evaluate the validity of heart rate index based on VO2max equations. Results: A significant correlation was observed between the criterion method of VO2max and HRindex-based VO2max equations (R=0.328, p<0.05). A significant difference (p<0.05) was observed between measured and HRindex-based VO2max equations (Mean difference = 3.34 - 5.45 ml/kg/min). In healthy adolescent boys, both estimation equations led to underestimation of VO2max by 11.36 ± 17.93% and 5.84 ± 16.39%, respectively. In addition, the Bland and Altman plot showed low agreement between measured and HRindex-based VO2max equations. Conclusions: HRindex-based VO2max equations do not have sufficient validity to be used in healthy adolescent boys and they led to the underestimation of VO2max. Therefore, it is recommended to employ HRindex-based VO2max equations for healthy adolescent boys.